2021
DOI: 10.3390/infrastructures6050069
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Reusing Damaged Steel Beams in Temporary Structures

Abstract: This study addresses the feasibility of reusing pre-damaged steel beams in temporary structures. The extensive structural investigation of notch-damaged, unrepaired, and laterally unsupported steel beams was performed experimentally and numerically. The simply supported specimens were tested in two-point loading with the study parameters being the location and size of the notch. Some beams had one notch on one edge of the tension flange at different locations, and some beams had two notches on both edges of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The software has a practical interface that makes the pre-processing step easy. The authors have utilized ATENA 3D in earlier works, see Mansour et al [30] and El-Ariss and Elkholy [31], due to…”
Section: Finite-element Modeling Of the Test Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The software has a practical interface that makes the pre-processing step easy. The authors have utilized ATENA 3D in earlier works, see Mansour et al [30] and El-Ariss and Elkholy [31], due to…”
Section: Finite-element Modeling Of the Test Beamsmentioning
confidence: 99%
“…The software has a practical interface that makes the pre-processing step easy. The authors have utilized ATENA 3D in earlier works, see Mansour et al [30] and El-Ariss and Elkholy [31], due to its high simulation capability. Moreover, the accuracy of numerical outcomes in this study confirmed the validity of this software.…”
Section: Finite-element Modeling Of the Test Beamsmentioning
confidence: 99%